2006
DOI: 10.1507/endocrj.k06-042
|View full text |Cite|
|
Sign up to set email alerts
|

Association of C-reactive Protein with Early-stage Carotid Atherosclerosis in Japanese Patients with Early-state Type 2 Diabetes Mellitus

Abstract: Abstract. The aim of this study was to assess the association between high sensitivity-C-reactive protein (hs-CRP), a sensitive marker of inflammation, and early-stage carotid atherosclerosis, in patients with early-state type 2 diabetes mellitus. The study subjects were 75 patients with type 2 diabetes mellitus without obvious diabetic vascular complications, who were not on any medication, and whose HbA 1c level was less than 6.5%. We evaluated the mean intima-media thickness (IMT) of the common carotid arte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…In agreement with previous studies [19,[22][23][24], we demonstrated that hypertension (high diastolic blood pressure) and dyslipidemia (low HDL-cholesterol level), components of metabolic syndrome, were associated with carotid IMT independently of known cardiovascular risk factors. Although, smoking is well known to be an independent risk factor of CVD, we failed to demonstrate the significant association between smoking status and carotid IMT in our study.…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with previous studies [19,[22][23][24], we demonstrated that hypertension (high diastolic blood pressure) and dyslipidemia (low HDL-cholesterol level), components of metabolic syndrome, were associated with carotid IMT independently of known cardiovascular risk factors. Although, smoking is well known to be an independent risk factor of CVD, we failed to demonstrate the significant association between smoking status and carotid IMT in our study.…”
Section: Discussionsupporting
confidence: 93%
“…It has been thought that serum hs‐CRP level leads to the development of atherosclerosis5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16. Although various new pharmacological approaches have been introduced to reduce hs‐CRP levels17, 18, 19, 20, 21, 22, 23, 24, 25, 26, there are still many cardiovascular diseases all over the world.…”
Section: Discussionmentioning
confidence: 99%
“…An increase of serum high‐sensitivity C‐reactive protein (hs‐CRP) level likely leads to the development of atherosclerosis. Indeed, it has been reported that hs‐CRP level is associated with carotid atherosclerosis in patients with type 2 diabetes mellitus5, 6, 7, 8, suggesting that hs‐CRP is a useful marker to predict an accelerated atherosclerotic process. It has also been shown that elevated hs‐CRP levels are associated with increased cardiovascular risk9, 10, 11, 12.…”
Section: Introductionmentioning
confidence: 99%
“…This proposed relationship between HbA 1c and CA 19-9 is supported by our study. Given that the inflammatory processes are important in etiology (27) as well as in complications of diabetes (28), these findings could be mediated through inflammation.…”
Section: Discussionmentioning
confidence: 99%